(untitled) (Global Journal of Medical Research, 2020)
Resume-The article includes materials on results of selection on breeding of Kyrgyz milk goats at several farms in different regions, characteristics on phenotypical peculiarities and productivity of breeds of different groups, as well as results of laboratory analyses of biochemical composition of goal milk.